Effectiveness of an environmental educational program on intern dentists’ knowledge and practices regarding eco-friendly green dentistry: a quasi-experimental study - Eman Helmy Hassan; Nesma Lotfy; Mamdouh Hanafy Abdou; Ebtisam Mohamed Fetohy; Mohamed Fakhry Hussein (BMC Medical Education)
Abstract Background The dental industry is associated with significant environmental impacts so there is a growing need for eco-friendly practices in dentistry. This study aimed to assess dental interns’ knowledge and practices regarding eco-friendly dentistry before and after the implementation of the environmental educational program. Methods An interventional quasi-experimental study (one group pre-test-post-test design) was conducted on 69 intern dentists at the Faculty of Dentistry Alexandria University. Assessment of knowledge and practices related to eco-friendly dentistry was performed three times: before, after two months, and after four months of the educational program. Results The mean age of participants was 23.72 years; 56.5% were males; 89.9% hadn’t received prior training on eco-friendly dentistry; and 40.6% obtained their green dentistry information from online websites. The educational program significantly improved their knowledge (median score percentage went from 50% before the intervention to 81.82% and 81.82% after two and four months of the conducting of the educational program, respectively.) and eco-friendly practices (median score percentage increased from 58.33% before the intervention to 75% and 66.67% after two and four months of the intervention, respectively) and the differences were statistically significant (p < 0.05). Significant positive correlations were noticed between knowledge and practice either before or after the training program (p < 0.05). Conclusions There was a significant improvement in knowledge and practices of the participants after the implementation of eco-friendly educational program. The successful educational program in early career is important in reducing waste generation and resource consumption, as well as potential cost savings on the long run. Clinical trial registration number PACTR202405544685014. Date: 20 May 2024, “retrospectively registered”.